Mineral exploration principles and applications - Haldar, S. K. (Elsevier, 2013)
Globally, mineral exploration has grown significantly in recent years, driven by the rapid acceleration in prices for gold and diamonds since 2004 and the emergence of a middle class in both China and India-aggressively increased demand. Despite this resurgence, no single book has been published that takes an interdisciplinary approach in addressing the full scope of mineral exploration-from mining and extraction to economic evaluation, policies, sustainability, and environmental impacts. Mineral Exploration: Principles and Applications accomplishes this by presenting each topic with.
Keywords: Prospecting.; Mines and mineral resources.; elektronické knihy; electronic books